2018
DOI: 10.1073/pnas.1802184115
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 3A1 activation prevents radiation-induced xerostomia by protecting salivary stem cells from toxic aldehydes

Abstract: SignificanceRadiation therapy for head and neck cancer often leads to dry mouth, a debilitating condition that affects speaking, swallowing, and other functions related to quality of life. Since salivary functional recovery after radiation is largely dependent on the number of surviving salivary stem/progenitor cells (SSPCs), we reasoned that protection of SSPCs from injury is critical for mitigating dry mouth. Following radiation, SSPCs accumulate toxic aldehydes that damage DNA, proteins, and lipids, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…A study reported another mechanism that IL-6/STAT3 pathway could be activated through ALDH3A1, contributing to reduced cell proliferation, migration, and invasion in oral squamous cell carcinoma [28], which was in consistent with our findings. However, several studies confirmed that ALDH3A1 was positively associated with tumor cells' progression, which was found in our research [29][30][31][32]. Also, BAG1 highly expressed in gallbladder carcinoma samples was inhibited by microRNA-138, increasing tumor cell proliferation [33].…”
Section: Discussionsupporting
confidence: 80%
“…A study reported another mechanism that IL-6/STAT3 pathway could be activated through ALDH3A1, contributing to reduced cell proliferation, migration, and invasion in oral squamous cell carcinoma [28], which was in consistent with our findings. However, several studies confirmed that ALDH3A1 was positively associated with tumor cells' progression, which was found in our research [29][30][31][32]. Also, BAG1 highly expressed in gallbladder carcinoma samples was inhibited by microRNA-138, increasing tumor cell proliferation [33].…”
Section: Discussionsupporting
confidence: 80%
“…However, some studies have shown that not all tumors exhibit high levels of ALDH3A1 expression, and the correlation between ALDH3A1 over-expression and estimation of tumor progression or prognosis may not be significant [22,23]. Saiki et al [24] indicated that higher ALDH3A1 protein levels in human head and neck cancer tumors were not associated with worse prognosis. Patel et al [25] reported that ALDH3A1 is expressed at higher levels in normal lung tissues in comparison to small cell lung cancer tissue.…”
Section: Ivyspringmentioning
confidence: 99%
“…Changes in the oral microenvironment are related to the radiation dose received by the parotid and submandibular glands 19 22 . Limiting the radiation dose to the parotid and submandibular glands can significantly reduce the risk and extent of xerostomia, while also protecting the oral microenvironment 20 , 23 . However, the exact dose limit for these glands is still unclear.…”
Section: Discussionmentioning
confidence: 99%